2023
DOI: 10.3389/fimmu.2023.1150828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NETs-related biomarkers and molecular clusters in systemic lupus erythematosus

Abstract: Neutrophil extracellular traps (NETs) is an important process involved in the pathogenesis of systemic lupus erythematosus (SLE), but the potential mechanisms of NETs contributing to SLE at the genetic level have not been clearly investigated. This investigation aimed to explore the molecular characteristics of NETs-related genes (NRGs) in SLE based on bioinformatics analysis, and identify associated reliable biomarkers and molecular clusters. Dataset GSE45291 was acquired from the Gene Expression Omnibus repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…We found that glucose metabolism‐related pathways were closely related to metabolism. Cluster analysis is a valuable tool that can categorize samples into specific groups based on gene transcription levels 28 . Clustering of 113 metabolism‐related gene sets clustered 453 COAD samples into two groups: CS1 and CS2 (Figure 7D).…”
Section: Resultsmentioning
confidence: 99%
“…We found that glucose metabolism‐related pathways were closely related to metabolism. Cluster analysis is a valuable tool that can categorize samples into specific groups based on gene transcription levels 28 . Clustering of 113 metabolism‐related gene sets clustered 453 COAD samples into two groups: CS1 and CS2 (Figure 7D).…”
Section: Resultsmentioning
confidence: 99%
“…Then, to identify important genes, we used the random forest (RF) algorithm and the least absolute shrinkage and selection operator (LASSO) analysis. LASSO analysis is a dimensionality reduction algorithm, and its accuracy is better than regression analysis 23,24 . The RF algorithm is a supervised learning method based on components that is frequently viewed as a decision tree extension 24,25 .…”
Section: Methodsmentioning
confidence: 99%
“…LASSO analysis is a dimensionality reduction algorithm, and its accuracy is better than regression analysis 23,24 . The RF algorithm is a supervised learning method based on components that is frequently viewed as a decision tree extension 24,25 . Finally, by merging the screening findings from the two analytical techniques, we were able to identify key PRGs.…”
Section: Methodsmentioning
confidence: 99%
“…Consensus clustering was employed to group the 590 CRC samples using the ConsensusClusterPlus package, 12 yielding distinct patient subgroups that were visually delineated, thereby illuminating intrinsic patterns within the data and underscoring the heterogeneity of the disease. 13,14 The pheatmap package (https://CRAN.R-project.org/ package=pheatmap) was utilized to construct a heatmap that compared the differences in clinical composition ratio between the two subgroups. PCA was conducted using the ggplot2 package to assess the ability of EMT survival-related differentially expressed genes in discriminating the two subgroups of CRC patients.…”
Section: Consensus Clustering Principal Component Analysis (Pca) and ...mentioning
confidence: 99%